The Persistent Effect of Competition on Prosociality - Fabian Kosse; Ranjita Rajan; Michela Tincani (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
We present the first causal evidence on the persistent impact of enduring competition on prosociality. Inspired by the literature on tournaments within firms, which shows that competitive compensation schemes reduce cooperation in the short-run, we explore if enduring exposure to a competitive environment persistently attenuates prosociality. Based on a large-scale randomized intervention in the education context, we find lower levels of prosociality for students who just experienced a 2-year competition period. 4-year follow-up data indicate that the effect persists and generalizes, suggesting a change in traits and not only in behavior.
Keywords: D64; C90; 330; prosociality; competition; cooperation; social skills; socio-emotional skills; tournaments; comparative pay; incentive schemes